Hadith of the Prophet in the Eyes of Sunni and Shia: An Analytical Study of Hadith and Tafsir Sciences - Nurrohman, Muhamad Ridwan (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2019)
This article aims to reexamine the foundational perspectives of Sunni and Shia views on Hadith. The main focus is on the Shia doctrine, which includes the infallible sayings (qaul ma'shum) of the Imams as part of the 'Prophetic' Hadith, which can be considered truthful. The occurrence of these sayings in key Shia Hadith texts is also notably problematic in number. In contrast to the sayings directly attributed to the Prophet or Ali, these collections are predominantly filled with the sayings of the sixth Imam, Ja'far al-Sadiq. Hence, the article discusses how robust this concept is when compared with the more widely accepted stance of the majority (jumhur).